Investigating the Influence of Kahoot on Students’ Vocabulary Acquisition in an EFL Context - Aulia Bela Marinda; Zakaria; Hariadi Syam; Ray Suryadi; Rais Abin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Vocabulary learning remains a central yet challenging component of English as a Foreign Language (EFL) instruction, particularly in contexts where classroom learning serves as the primary source of language exposure. Traditional teaching approaches often rely on memorization and translation, which may not effectively promote active learning or long-term retention. The purpose of this study is to investigate the impact of the Kahoot gamified learning platform on students’ vocabulary acquisition in an EFL context. A quasi-experimental pretest–posttest design was conducted with two intact tenth-grade classes at SMK Negeri 2 Kolaka, consisting of 30 students in the experimental group and 30 in the control group. The treatment was implemented over six meetings using a 25-item multiple-choice vocabulary test with high reliability (Cronbach’s α = 0.940). T-tests for independent and paired samples were used to analyze the data, identifying within-group improvements and between-group differences. The findings indicated that the experimental group taught through Kahoot achieved significantly higher post-test scores than the control group (p < 0.05). The results suggest that integrating Kahoot as a gamified learning platform can enhance students’ vocabulary mastery, increase engagement, and foster a more interactive learning environment in EFL classrooms. These results underscore the capability of Kahoot-based instruction to extend current understanding of digital gamification in EFL vocabulary teaching by demonstrating measurable gains in learner outcomes.